Une Salle de bain qui décline sa nationalité. Jean-Philippe Toussaint : écrivain belge - Almeida, José Domingues de (2018)
This paper suggests a national identity reading (Belgian Francophone) of the novel La salle de bain (1985) by « French » writer Jean-Philippe Toussaint.